A foreign body masquerading as a tumour. (22nd January 2013) - Maempel, Julian Frederick; Nicol, Graeme; Clement, Rhys Gareth Ellis; Porter, Daniel
Abstract : A 29-year-old man presented to his local orthopaedic service with a mass in the medial aspect of his left thigh, present for 1 year. It had not changed in size, although he complained of increasing tightness in the region. He denied any systemic symptoms or history of local trauma. Extensive imaging performed at his local hospital was thought suggestive of a musculoskeletal tumour. The patient was referred to our tertiary centre musculoskeletal tumour clinic. Review of external imaging and further investigations revealed a fluid-filled intramuscular mass containing an echogenic focus consistent with foreign body. Ultrasound-guided aspiration yielded fluid which grew Staphylococcus aureus . Only when presented with this information did the patient vaguely recall sitting on a wooden kebab stick 30 months previously. At surgery, a thick-walled abscess with a central foreign body was identified and drained. At follow-up 1 month later, he was well with no recurrent problems.